IMPLEMENTASI PROGRAM ROLE MODEL DALAM MEMBENTUK KARAKTER DISIPLIN DIKALANGAN SISWA SD - Dhiya Nasywa; Andimas Renda Kevindo; Sigit Wibowo; Erif Ahdhianto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Character education, especially discipline, is an important foundation in forming a responsible and independent young generation. This study aims to analyze the implementation of role models in building the disciplined character of fourth-grade students at SDN 2 Karangan, Trenggalek Regency. A qualitative approach was used with observation, interview, questionnaire, and documentation methods. The results showed that student discipline was at a high level, indicated by 71% of students arriving on time, 79% wearing complete uniforms, and 86% paying serious attention to the teacher's explanation. Teachers play an important role as role models in instilling the values of discipline through role models, such as punctuality, neatness, and consistency in rules. This study also identified supporting and inhibiting factors in the implementation of role models, including the importance of collaboration between teachers, parents, and the school environment. Strategic steps such as providing real examples, building positive relationships, and ongoing evaluation have proven effective in internalizing the values of discipline. These findings confirm that the role model program is a practical and relevant approach to forming the disciplined character of elementary school students, which is the foundation for their future success.